Geological Model of Khasib Reservoir- Central Area/East Baghdad Field - Al-Jawad, Mohammed Saleh; Kareem, Khalid Ahmed (Iraqi Journal of Chemical and Petroleum Engineering, 2016)
The Geological modeling has been constructed by using Petrel E&P software to incorporate data, for improved Three-dimensional models of porosity model, water saturation, permeability estimated from core data, well log interpretation, and fault analysis modeling.Three-dimensional geological models attributed with physical properties constructed from primary geological data. The reservoir contains a huge hydrocarbon accumulation, a unique geological model characterization with faults, high heterogeneity, and a very complex field in nature.The results of this study show that the Three-dimensional geological model of Khasib reservoir, to build the reservoir model starting with evaluation of reservoir to interpretation of well log by using IP software for 14 wells, defining and divided the layers based on the GR Log and Resistivity log to nine layers and then maintained the fault model for a divided central area to four regions. Compared porosity log with porosity core to estimate correction porosity and enter this value to predict the permeability value for each layer by using FZI, and RQI method. The model Containing faults, horizons, zones, and layers depending on this data to make gridding by using pillar gridding.This paper presents a geological modeling and an uncertainty analysis for stock-tank original oil in place. The distribution of the faults is also discussed.